KNOWLEDGE, ATTITUDES, AND PRACTICES TOWARDS COVID-19 AMONG RESIDENTS IN HAIL CITY, SAUDI ARABIA: A CROSS-SECTIONAL STUDY - ALSHAMMARI, FARHAN; ALHAGBANI, TURKI; ALAFNAN, AHMED; ALMANSOUR, KHALID; KHAN, KASHIFULLAH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Immense measures were taken to monitor the rapid spread of the novel coronavirus disease (COVID-19) outbreak in Saudi Arabia. Knowledge, attitudes, and practices (KAPs) against COVID-19 influence a resident’s commitment to these control measures. The objective of the study was to investigate the KAP of Saudi residents toward COVID-19 during the increasingly growing outbreak period. Methods: Through the authors’ network with residents in Hail city and the northern region of Saudi Arabia, an online sample was successfully carried out among Saudi residents. The participants completed an established and validated online KAP questionnaire. The knowledge questionnaire consisted of 16 questions regarding the clinical characteristics and prevention of COVID-19. Assessments of attitudes and practices of the residents toward COVID-19, included questions on confidence in controlling the COVID-19 outbreak, going to crowded places and wearing facemasks when going out in recent days. Results: A total of 285 participants took part in the survey questionnaire, of these 54.7% were women, 68.4% held a bachelor’s degree, and 47.7% were engaged in an occupation other than health-care providers. The overall correct rate of the knowledge questionnaire was 65%. The majority of the respondents (66%) reported that they had confirmed the information obtained from different media sources, where nearly 78.3% of respondents agreed that COVID-19 can be successfully controlled. Furthermore, about 92.3% of the participants avoided going out to crowded places, whereas only 41.1% wore facemasks when going out in recent days. A statistically significant association (p=0.0001) was found on analysis of the COVID-19 knowledge score, with a lower likelihood of negative attitudes and preventive practices toward COVID-2019. Conclusion: The majority of Hail city residents are familiar with COVID-19 in both genders, hold optimistic attitudes, and have appropriate practices toward COVID-19. Health education programs designed to enhance COVID-19 awareness are beneficial for Saudi residents to maintain positive attitudes and appropriate practices.